Pengaruh Kesadaran Wajib Pajak, Kualitas Pelayanan dan Sistem Samsat Drive Thru Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Moch Romadhon; Ontot Murwanto (Jurnal Riset Ekonomi dan Akuntansi, 2024)
The main source of state revenue is taxation, and one of them is motor vehicle tax. Respecting tax duties, like paying money for public welfare, is a constructive contribution. The aim of the following research is to understand how the SamSat drive through system, service quality, and taxpayer awareness influence motor vehicle tax compliance. Distributing questionnaires to samples that have been determined in Samsat throughout Surabaya City is a technique for collecting data in the following research. The sampling method selects a random sample of vehicle tax payer respondents. The sample consisted of 90 people. The findings show that SAMSAT drive thru, service quality, and, knowledge, of mandatory, taxes, all contribute to better vehicle tax compliance. In the city of Surabaya, the drive thru samsat system (0.027 < 0.05), service quality (0.008 < 0.05), and taxpayer awareness (0.000 < 0.05) all have a good impact on motor vehicle taxpayer compliance.